EFFECTIVENESS OF BORON APPLICATION: SOIL VS FOLIAR FEEDING - PRATIBHA THAKUR; PARDEEP KUMAR (The Bioscan, 2021)
High yielding cultivars, are highly exhaustive but macronutrient status of the soils is little affected due to almost matching external replenishment of these nutrients. However the supply of micronutrients to soil is negligible, and organic manures, considered as the main source of micronutrients have been replaced by high analysis, nutrient specific fertilizers resulting in over mining from the soil at an alarming. Boron is one of the most important and deficient micronutrient in Indian soils. Boron performs a key role in diverse range of plant functions including cell wall formation and is essential for cell wall division, accelerating growth, sugar translocation, development, enhancing yield and upgrading crop quality. As boron is involved in pollination, and fruit and seed development, its requirements are much higher for reproductive growth. Even under adverse conditions, boron acts as a stress buster and helps the crops to survive. It also helps in improving the nutrient use efficiency of plants. Despite having unlimited advantages in crop production, boron is an underdog among micronutrients. Right sources, timing, methods and rates of boron application are not well established therefore it is considered as a trivial element and need focus in harnessing higher production and crop quality.